Effect of Low-Density Lipoprotein Cholesterol Goal Achievement on Vascular Physiology Evaluated by Quantitative Flow Ratio in Patients Who Underwent Percutaneous Coronary Intervention - Chen, Long; Chen, Qin; Zhong, Jiaxin; Ye, Zhen; Ye, Mingfang; Yan, Yuanming; Chen, Lianglong; Luo, Yukun (Frontiers in Cardiovascular Medicine, 2021)
Purpose: The change in coronary physiology from lipid-lowering therapy (LLT) lacks an appropriate method of examination. Quantitative flow ratio (QFR) is a novel angiography-based approach allowing rapid assessment of coronary physiology. This study sought to determine the impact of low-density lipoprotein cholesterol (LDL-C) goal achievement on coronary physiology through QFR. Methods: Cases involving percutaneous coronary intervention (PCI) and 1-year angiographic follow-up were screened and assessed by QFR analysis. Patients were divided into two groups according to the LDL-C level at the 1-year follow-up: (1) goal-achievement group (LDL-C < 1.8 mmol/L or reduction of ≥50%, n = 146, lesion = 165) and (2) non-achievement group (n = 286, lesion = 331). All QFR data and major adverse cardiovascular and cerebrovascular events (MACCEs) at 1 year were compared between groups. Results: No differences between the groups in quantitative coronary angiography (QCA) data or QFR post-PCI were found. At the 1-year follow-up, lower percentage diameter stenosis (DS%) and percentage area stenosis (AS%) were recorded in the goal-achievement group (27.89 ± 10.16 vs. 30.93 ± 12.03, p = 0.010, 36.57 ± 16.12 vs. 41.68 ± 17.39, p = 0.003, respectively). Additionally, a better change in QFR was found in the goal-achievement group (0.003 ± 0.068 vs. −0.018 ± 0.086, p = 0.007), with a lower incidence of physiological restenosis and MACCEs (2.1 vs. 8.4%, p = 0.018, 5.4 vs. 12.6%, p = 0.021, respectively). Conclusion: Evaluated by QFR, patients who achieved the LDL-C goal appear to have a better coronary physiological benefit. This group of patients also has a better clinical outcome.